RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1. (15th July 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstrct: Summary: The existing information supports the use of this material as described in this safety assessment. Cinnamyl alcohol was evaluated for genotoxicity, repeated dose toxicity, developmental toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization, and environmental safety. Data show that cinnamyl alcohol is not genotoxic. Data on read-across analog cinnamaldehyde (CAS # 104-55-2) provide a calculated margin of exposure (MOE) >100 for the repeated dose and local respiratory toxicity endpoints. The developmental and reproductive toxicity endpoint was evaluated using the threshold of toxicological concern (TTC) for a Cramer Class I material, and the exposure to cinnamyl alcohol is below the TTC (0.03 mg/kg/day). Data provided a No Expected Sensitization Induction Level (NESIL) of 2900 μg/cm 2 for the skin sensitization endpoint. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; cinnamyl alcohol is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; cinnamyl alcohol was found not to be persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental Concentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: Cinnamyl alcohol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.